Nilai-Nilai Pendidikan tentang Ahklak Siswa terhadap Guru dalam Kitab Ahklak Lil Banin Jilid II Karangan Syekh Umar Bin Ahmad Baradja - Fachrurozi Kamal, Muhamad Faqih; Surana, Dedih; Al Ghazal, Sobar (UNISBA Press, 2024)
Abstract. Moral education is the core of all types of education. Because morals are education that directs the creation of human inner and outer behavior so that it becomes a balanced human being in the sense of himself and outside himself. The position of morals in human life occupies an important place. if the morals are good, then the physical and mental well-being, if the morals are damaged, then the physical and mental damage. The glory of a person lies in good morals, good morals always make a person safe, calm and no reprehensible actions. Of the many books that discuss adab education, the author chooses the book of akhlak lil banin as a reference and also analyzes the adab of students towards teachers. Based on this phenomenon, the problems in this study are formulated as follows: (1) What is the essence of student manners towards teachers in the book of morals lil-banin volume II by Sheikh Umar bin Ahmad Baraja? (2) What are the views of education experts on student manners towards teachers? (3) The educational values of student manners towards teachers contained in the book of morals lil-banin volume II by Sheikh Umar bin Ahmad Baraja? The research objectives are as follows: (1) To find out the essence of students' morals towards teachers in the book of morals lil-banin volume II by Sheikh Umar bin Ahmad Baraja. (2) To find out the views of education experts about students' morals towards teachers. (3) To find out the values of ahklak education. Abstrak. Pendidikan akhlak adalah inti dari semua jenis pendidikan. Karena akhlak merupakan pendidikan yang mengarahkan pada terciptanya perilaku lahir dan batin manusia sehingga menjadi manusia yang seimbang dalam arti terhadap dirinya maupun luar dirinya. Kedudukan akhlak dalam kehidupan manusia menempati tempat yang penting. apabila akhlak baik, maka sejahteralah lahir dan batinnya, apabila akhlaknya rusak, maka rusaklah lahir dan batinnya. Kejayaan seseorang terletak pada akhlak yang baik, akhlak yang baik selalu membuat seseorang menjadi aman, tenang dan tidak ada perbuatan yang tercela. Dari banyak kitab yang membahas tentang pendidikan adab, penulis memilih kitab akhlak lil banin sebagai rujukan dan juga analisis adab murid terhadap guru. Berdasarkan fenomena tersebut maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana esensi akhlak siswa terhadap guru dalam kitab ahklak lil-banin jilid II karangan syeikh Umar bin Ahmad Baraja? (2) Bagaimana pandangan ahli pendidikan tentang ahklak siswa terhadap guru? (3) Nilai-nilai pendidikan ahklak siswa terhadap guru yang terkandung dalam kitab akhlak lil-banin jilid II karangan syeikh Umar bin Ahmad Baraja? Adapun tujuan penelitian sebagai berikut: (1) Untuk mengetahui esensi akhlak siswa terhadap guru dalam kitab ahklak lil-banin jilid II karangan syeikh Umar bin Ahmad Baraja. (2) Untuk mengetahui pandangan ahli pendidikan tentang ahklak siswa terhadap guru. (3) Untuk mengetahui nilai-nilai pendidikan.